Use of Race in Maternal–Fetal Medicine Research. Issue 5 (September 2022) - Wisner, Kirsten
Abstract : The Society for Maternal-Fetal Medicine published a special statement that urges a critical examination of how race is used in maternal-fetal medicine research. Our maternity nursing expert, Dr. Wisner, summarizes the statement and offers suggestions for application to appraisal of research and practice evidence.